Analisis Semantik Kata Pernikahan di dalam Al-Qur’an dan Relevansinya terhadap Fenomena Ketakutan Menikah - Wanto, Sugeng; Damanik, Agusman; Putra, Muhammad Rizky Adriansyah (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2025)
This study aims to analyze the meaning of the word marriage in the Qur'an using a semantic approach developed by Toshihiko Izutsu. This approach includes an analysis of basic meaning, relational meaning, the structure of meaning in the Qur'anic value system (weltanschauung), as well as a comparison of pre-Qur'anic and Qur'anic meanings. This study uses a phenomenological method with a literature study strategy to explore the meaning of words in the text of the Qur'an while reflecting on the social experiences that develop in society. The results of the study show that the meaning of the word marriage from the pre-Qur'anic to the post-Qur'anic period remains consistent as a sacred and legal bond or agreement between two individuals. The Qur'an emphasizes that marriage aims to create a sakinah, mawaddah, and rahmah domestic life. However, in the contemporary social context, this meaning is distorted due to dysfunctional experiences in the family, inequality in gender relations, and the influence of negative narratives on social media. The phenomenon of fear of marriage is not a rejection of sharia, but a response to social failure in realizing Qur'anic values in an applicative manner.